2016
DOI: 10.1007/978-3-319-33714-2_45
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Design of a Cable Driven Parallel Mechanism for Planar Earthquake Simulation

Abstract: Earthquake simulation is helpful in order for society to experience real seismic waves in safe environment. Cable-driven parallel mechanisms have advantages over conventional serial and parallel mechanisms. Prototype simulator which covers 1 m stroke in each direction has been built. In this paper, conceptual design of an earthquake simulator using cable driven parallel mechanism is presented. Spatial arrangement of cables is investigated in terms of the stability and safety of the simulator by dynamic analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Research on serial robots has found several applications in exoskeletons and prosthetics. [8][9][10][11] The parallel robot has different names such as cable parallel robot (CPR), 12 cable-driven parallel robot (CDPR), 13 cable-driven parallel manipulator (CDPM), 14 cabledriven planar parallel manipulator (CDPPM), 15 cableactuated parallel manipulator (CPM), 16 and cabledriven parallel platform with a pneumatic muscle active support (CPPPMS). 17 Differential cable-driven type has found several applications in humanoid robots for its higher load capability and relatively more compact structure, but do not fall into the category of serial and parallel robots.…”
Section: Introductionmentioning
confidence: 99%
“…Research on serial robots has found several applications in exoskeletons and prosthetics. [8][9][10][11] The parallel robot has different names such as cable parallel robot (CPR), 12 cable-driven parallel robot (CDPR), 13 cable-driven parallel manipulator (CDPM), 14 cabledriven planar parallel manipulator (CDPPM), 15 cableactuated parallel manipulator (CPM), 16 and cabledriven parallel platform with a pneumatic muscle active support (CPPPMS). 17 Differential cable-driven type has found several applications in humanoid robots for its higher load capability and relatively more compact structure, but do not fall into the category of serial and parallel robots.…”
Section: Introductionmentioning
confidence: 99%